Types of struggles represented on the first character of “Maquia: When The Promised Flower Blooms” - Wibowo, Khrisna Cahya; Probowati, Yeni; Duwila, Shanty (EL2J (English Language and Literature Journal), 2024)
The primary aim of this research is to thoroughly analyze the various types of struggles faced by the main character, Maquia, in the animated movie Maquia: When the Promised Flower Blooms. To achieve this objective, the writer employed a qualitative research method, in order to find the type of struggles that Maquia encounters throughout the narrative. The source material for this research was the movie itself, which was obtained from the internet via the website: https://kusonime.com. The data collection process involved several key steps: first, downloading the movie Maquia: When the Promised Flower Blooms; second, watching the film attentively; and third, taking detailed notes on the dialogues and scenes that specifically depict the types of struggles faced by Maquia. Through this analysis, the writer identified three distinct types of struggles based on Georgia’s struggle theory: Man vs. Self, Man vs. Society, and Man vs. Fate or Destiny. These struggles are evident in various aspects of Maquia’s journey, particularly highlighting the challenges she faces as a single mother. Ultimately, the research concludes that the struggles depicted in Maquia’s story serve as a poignant representation of the profound difficulties associated with single motherhood, underscoring the emotional and societal challenges that accompany this role.